Early Shiite hermeneutics and the dating of Kitāb Sulaym ibn Qays. (17th March 2015) - Gleave, Robert
Abstract The Kitāb Sulaym ibn Qays, a collection of sayings attributed to ʿAlī b. Abī Ṭālib, was supposedly collected by the (otherwise unknown) Sulaym b. Qays al-Hilālī (d. 76/678); the work is generally recognized as an important source for early Shīʿī thought. There has been much debate, both within the Shīʿī tradition and outside of it, over when its contents reached their current form and how representative they were of Shīʿī views in the early centuries of Islam. Here, I take one passage from the Kitāb Sulaym and set it against the development of early Muslim hermeneutics in an attempt to establish a tentative dating for this passage. The result is a dating between late eighth century ce (second century ah) and the early ninth century ce (early third century ah), roughly contemporary with, and perhaps postdating the revolutionary hermeneutic work of Muḥammad b. Idrīs al-Shāfiʿī (d. 204/820). This conclusion tallies, to some extent, with an analysis of the report's various isnāds.